Human α-thrombin detection platform using aptamers on a silicon nanowire field-effect transistor - Römhildt, Lotta; Zörgiebel, Felix; Ibarlucea, Bergoi; Vahdatzadeh, Maryam; Baraban, Larysa; Cuniberti, Gianaurelio (Giovanni); Pregl, Sebastian; Weber, Walter M.; Mikolajick, Thomas; Opitz, Jörg (2017 27th International Symposium on Power and Timing Modeling, Optimization and Simulation, PATMOS 2017, 2017)
We present a silicon nanowire-based field-effect transistor biosensor with Schottky barriers for highly specific and sensitive human α-thrombin detection. The active sensor area is decorated with thrombin-binding aptamers as receptor molecules. Each sensor chip is integrated into a microfluidic device for flow-through measurements. Instantaneous detection is provided by real-time monitoring of FET transfer curves. With this approach, thrombin concentrations between 200 pM and 200 nM are detected in a label-free, real-time manner, covering a wide dynamic range and enabling to distinguish between healthy and pathological levels. The development of simple, miniaturized devices for blood protein detection is highly interesting for medical diagnostics.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Aptamers; Aptasensors; Field effect transistor; Human α-thrombin; Silicon nanowires